The effects of angiotensin-converting enzyme inhibitors and angiotensin II receptor blockers in critically ill patients with acute kidney injury: An observational study using the MIMIC database - Zhu, Xu; Xue, Jing; Liu, Zheng; Dai, Wenjie; Xiang, Jingsha; Xu, Hui; Zhou, Qiaoling; Zhou, Quan; Wei, Xinran; Chen, Wenhang (Frontiers in Pharmacology, 2022)
Background: The safety of prescribing angiotensin-converting enzyme inhibitors (ACEIs) and angiotensin receptor blockers (ARBs) during acute kidney injury (AKI) remains unclear. We aimed to investigate the associations of ACEI/ARB therapy in AKI with the risk of mortality, acute kidney disease (AKD), and hyperkalemia. Methods: We conducted a retrospective propensity score-matched cohort study, which included patients from the Medical Information Mart for Intensive Care IV (MIMIC-IV) database. The association between ACEI/ARB therapy and mortality was assessed using Cox proportional hazards regression models. Logistic regression was used to assess the risk of AKD and hyperkalemia. Results: Among the 19,074 individuals with AKI admitted to the intensive care unit (ICU), 12,090 (63.4%) received ACEI/ARBs, while 6,984 (36.6%) did not. In the propensity score-matched sample of 10,300 individuals, we found a decreased risk of mortality in those who received ACEI/ARBs compared to those who did not (hazard ratio [HR] for ICU mortality: 0.63, 95% confidence interval [CI]: 0.54–0.73); HR for in-hospital mortality: 0.72, 95% CI: 0.64–0.80; HR for 30-day mortality: 0.73, 95% CI: 0.66–0.81; HR for 180-day mortality: 0.75, 95% CI: 0.67–0.82). However, the use of ACEI/ARBs was associated with a higher risk of AKD (risk ratio [RR]: 2.90; 95% CI: 2.49–3.37). Patients who received ACEI/ARBs in the ICU were also at a greater risk for hyperkalemia compared to those who did not (RR: 1.37; 95% CI: 1.13–1.67). Conclusions: ACEI/ARB treatment during an episode of AKI may decrease all-cause mortality, but increases the risk of AKD and hyperkalemia. Future randomized controlled trials are warranted to validate these findings.